Independent Learning Curriculum: Readiness of Teachers and Madrasah in Bone Regency - Azis, Muhammad Bachtiar; Fitriani, Fitriani; Amin, Arifah; Nurul Kamila, Adinda (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2024)
This study aims to determine the madrasah readiness in implementing the Independent Learning Curriculum (Kurikulum Merdeka Belajar). The research applies a mixed-method approach, specifically a combination of qualitative and quantitative research with the concurrent triangulation strategy model. Data collection techniques involve interviews, questionnaires, and documentation. The research findings are as follows: 1) Teachers' readiness in implementing the Independent Learning Curriculum, encompassing dimensions such as a) teachers' knowledge falls into the